2018
DOI: 10.3389/fcomm.2018.00052
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism in a Case of the Non-fluent/agrammatic Variant of Primary Progressive Aphasia

Abstract: There is a growing body of research on language impairment in bilingual speakers with neurodegenerative diseases. Evidence as to which language is better preserved is rather inconclusive. Various factors seem to influence language performance, most notably age of acquisition, level of proficiency, immersion and degree of exposure to each language. The present study examined fluency, lexical, discourse and grammatical abilities of a Greek-French late bilingual man with the non-fluent/agrammatic variant of prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…The MAIN [ 38 ] is a tool designed to evaluate narrative tell and retell skills in children but has also been used with adults with acquired language deficits associated with neurological disease for research purposes [ 46 ]. The MAIN stories consist of coloured picture sequences developed according to strict psycholinguistic criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The MAIN [ 38 ] is a tool designed to evaluate narrative tell and retell skills in children but has also been used with adults with acquired language deficits associated with neurological disease for research purposes [ 46 ]. The MAIN stories consist of coloured picture sequences developed according to strict psycholinguistic criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure was employed for the analysis of two narrative productions from a picture description task ("Cookie Theft" from the BDAE) and a story retell task (from the Multilingual Assessment Instrument for Narratives -MAIN) (Gagarina et al, 2019). Detailed information about the QPA and the connected speech analysis procedure employed in this study can be found in Karpathiou et al (2018).…”
Section: Linguistic Assessmentmentioning
confidence: 99%
“…While a lot of work and research has been done on psycholinguistic research over the recent years in Cyprus (e.g., Anyfantis et al, 2023;Charalambous et al, 2023;Grohmann et al, 2021;Karpathiou et al, 2018;Theodorou et al, 2022;Tsiplakou et al, 2022) and words are widely used as stimuli in research (Baddeley et al, 1975;Healey et al, 2018;Traikapi et al, 2022;White et al, 2014), there is a notable lack of such resources available for Greek-Cypriots. The absence of standardized word pools presents a substantial challenge, when conducting research that relies on serial cognitive assessments using alternate test forms.…”
Section: Introductionmentioning
confidence: 99%